Social network methodology for studying HIV epidemiology in men having sex with men - Shui Shan Lee; Dennise Ka Po Tam; Raymond Lei Ming Ho; Ka Hing Wong (Elsevier, 2009)
A self-administered network-based questionnaire survey was conducted on 91 HIV-positive Chinese men having sex with men (MSM). Affiliation matrices were created to assess their networking pattern. The individuals' preferential use of venues for sex partnership before HIV infection has changed over three time periods of 1997-2000, 2001-2003 and 2004-2006. Over time, there was a parallel increase in network density (density scores from 0.26, through 0.36, to 0.53) and degree centrality (from a median score of 9, through 12, to 16), suggesting that connectivity of MSM was becoming higher through sexual networks. The overall practice of unprotected sex has, however, remained the same. The study demonstrated how the application of social network analysis could enrich the epidemiologic description of HIV infection in the population. Keywords: HIV, Men having sex with men, MSM, Social network analysis